2018
DOI: 10.3324/haematol.2017.185991
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II dose-escalation study investigating all-oral ixazomib-melphalan-prednisone induction followed by single-agent ixazomib maintenance in transplant-ineligible newly diagnosed multiple myeloma

Abstract: This phase I/II dose-escalation study investigated the all-oral ixazomib-melphalan-prednisone regimen, followed by single-agent ixazomib maintenance, in elderly, transplant-ineligible patients with newly diagnosed multiple myeloma. Primary phase I objectives were to determine the safety and recommended phase II dose of ixazomib-melphalan-prednisone. The primary phase II objective was to determine the complete plus very good partial response rate. In phase I, patients were enrolled to 4 arms investigating weekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
(67 reference statements)
1
16
0
Order By: Relevance
“…Last, in the time after the study period, the FDA has approved additional chemotherapy agents for MM (eg, carfilzomib, ixazomib, daratumumab). However, in upfront clinical trials, these agents have not been associated with high rates of VTE . In summary, we developed and validated the IMPEDE VTE score, which outperformed the risk stratification in the IMWG/NCCN guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Last, in the time after the study period, the FDA has approved additional chemotherapy agents for MM (eg, carfilzomib, ixazomib, daratumumab). However, in upfront clinical trials, these agents have not been associated with high rates of VTE . In summary, we developed and validated the IMPEDE VTE score, which outperformed the risk stratification in the IMWG/NCCN guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, single-agent ixazomib maintenance has been utilized following ixazomib-based induction in four phase 1/2 studies 45,[80][81][82][83] ; a pooled analysis of maintenance patients from these studies reported deepening responses in 23% of patients, as well as a median PFS of 21.4 months and a 3-year OS of 82% from the start of maintenance, with limited new-onset AEs 84 . Ixazomib-daratumumabdexamethasone followed by ixazomib maintenance is being evaluated in unfit and frail patients in the phase 2 HOVON-143 study, which has reported promising safety and response data for the induction phase 85 .…”
Section: Maintenance Therapy Post-induction In the Nontransplant Settingmentioning
confidence: 99%
“…The four trials have been reported in full prev iously. [24][25][26][27][28] Briefly, patients received weekly or twiceweekly ixazomib plus Rd (IRd, C16005, and C16008, respectively), weekly or twice-weekly ixazomib plus melphalan-prednisone (IMP, C16006), or weekly ixazomib plus cyclophosphamide-dexamethasone (ICd, C 16020), as induction treatment, followed by singleagent ixazom ib maintenance. Full details of induction treatment are summariz ed in the Supporting Information section.…”
Section: Included Studiesmentioning
confidence: 99%
“…Among the 59 patients who received ixazomib maintenance at the weekly RP2D of 4.0 mg, the median PFS from start of maintenance was 25.3 months, as determined in two of the original source studies. 24,26 In addition to the TOURMALINE-MM3 study, 23 the TOURMALINE-MM4 (NCT02312258), a phase III, double-blind, placebo-controlled study, is evaluating maintenance treatment in patients with NDMM, who have responded to any induction therapy but have not undergone ASCT. As in TOURMALINE-MM3, an initial weekly dose of 3.0 mg is used, as patients have not been previously exposed to ixazomib; this dose may be escalated to 4.0 mg after 4 cycles in the absence of significant toxicity.…”
Section: Myocardial Infarction 1 (<1)mentioning
confidence: 99%
See 1 more Smart Citation